IMPROVING THE QUALITY OF HUMAN RESOURCES IN HAJJ AND UMRAH MANAGEMENT: THE KEY TO SUCCESSFUL PILGRIMAGE SERVICES - Yesi Suhartini; Oggy Akmadani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Human Resource (HR) quality improvement in Hajj and Umrah management refers to a systematic and continuous effort to improve the knowledge, skills, and attitudes of Hajj and Umrah service officers and managers. This includes a series of processes ranging from recruitment, training, competency development, to performance evaluation that aim to ensure that every personnel involved in organising Hajj and Umrah has adequate capacity to provide excellent service to pilgrims. Improving the quality of human resources does not only focus on the technical aspects of service, but also includes a deep understanding of the spiritual, cultural, and ethical values that form the basis for the implementation of Hajj and Umrah, so as to produce human resources who are not only professional in their duties, but also have high integrity and dedication in serving pilgrims. The results show that a comprehensive HR development programme should include improving ritual knowledge, management skills, foreign language ability, cross- cultural understanding, and soft skills. The use of information technology in training and performance management was also found to be an important factor in optimising HR quality. The research also underlines the importance of establishing an organisational culture that is oriented towards service excellence and continuous improvement. Thus, this study emphasises that investment in HR development has a direct impact on improving service quality, pilgrims' satisfaction, and the efficiency of Hajj and Umrah operations.